The text of Silvio Pellico's "Francesca da Rimini" (Prassi Ecdotiche della Modernità Letteraria, 2017)
The aim of this piece is to bring order to the rich tradition of Silvio Pellico’s tragedy Francesca da Rimini, brought to stage since 1815. The analysis focuses on three autograph manuscripts and on the first two editions. The occurrence of marginalia, which are not in the author’s hand (among them, Ugo Foscolo’s), in two manuscripts, has been investigated and placed in relation to the tragedy’s following drafts; a new dating is proposed for the third manuscript, as transcribed far in time from the first theatrical performance. In 1818 two editions were printed, both in two issues: a non-authorized one, and the one approved by Pellico. The comparison between these two editions and the collation of several copies of the princeps allowed to determine its issues’ chronological sequence, and the final authorial intention.
Keywords: Silvio Pellico; Francesca da Rimini; Ugo Foscolo; Ludovico di Breme; autographs; manuscripts; editions; variants; author's last will; autorial intention